A Tale of Two Teachers: A Duoethnography of the Realistic and Idealistic Successes and Failures of Teaching English as An International Language. (April 2018) - Rose, Heath; Montakantiwong, Anuchaya
With the growth of English worldwide there have been numerous calls for a paradigm shift from teaching English as foreign language to teaching English as an international language (EIL). While there is a growing body of conceptual literature for teaching EIL, the voices of teachers remain severely underrepresented in this movement. As such, current EIL research is missing the perspective of this key stakeholder, who is in a prime position to report 'on-the-ground' challenges of integrating EIL approaches into English language classrooms. This article addresses this gap by offering an in-depth joint autoethnography of two English language teachers, who actively experimented with EIL-informed pedagogy at universities in Japan and Thailand, and who provide very different tales of the resulting challenges and successes. Data was collected via a duoethnographic approach, an innovative methodology which presents two juxtaposing dialogic narratives in order to show readers in-depth, personal and autobiographical accounts from both teachers' experiences. Analysis of these narratives provides an illustration of the issues surrounding the implementation of research-informed innovations into ELT classrooms. The findings are discussed in terms of whether teaching EIL is a possible reality, or whether it remains an ideological fantasy.